Erratum to An Alternative Approach to Ethical HRM Through the Discourse and Lived Experiences of HR Professionals (J Bus Ethics, 10.1007/s10551-012-1479-z) - de Gama, N.; McKenna, Stephen; Peticca-Harris, A. (Springer Netherlands, 2012)
The above mentioned article was accepted as ‘An alternative approach to ethical HRM through the discourse and lived experiences of HR professionals’. During proof stage the title was changed to ‘Ethics and HRM: Theoretical and Conceptual Analysis; An Alternative Approach to Ethical HRM Through the Discourse and Lived Experiences of HR Professionals’ without approval of the guest editors. The original title ‘An alternative approach to ethical HRM through the discourse and lived experiences of HR professionals’ it to be used when referring to this article in other works.